Analisis Aspek Emosi Yesaya dalam Perjumpaan Allah: Studi Eksegesis Yesaya 6 - Denis Andrian; Farel Yosua Sualang (Phronesis: Jurnal Teologi dan Misi, 2025)
This article examines the aspect of emotions experienced by the prophet Isaiah in his encounter with God, described in Isaiah 6:1-8. This research is motivated by the lack of in-depth analysis of Isaiah's emotional aspects in the narrative, particularly using the 'Voice of the Bible' approach. Jill Middlemas, examines the emotional aspects of Isaiah's prophetic calling, but has not specifically highlighted the dynamics of Isaiah's emotional transition in encountering God. The research methodology involved textual analysis using an exegetical approach to Isaiah 6:1-8, including the study of key Hebrew words related to voice and emotion. Narrative analysis was used to identify the stages of the narrative and the emotions associated with each stage. In addition, a brief comparative analysis with call narratives from other prophets was conducted to provide a broader context. This research utilizes an interdisciplinary approach, combining perspectives from biblical studies, psychology, and spirituality. The significance of this research lies in its contribution to a deeper understanding of spiritual experience and its implications for contemporary spiritual life. By analyzing Isaiah's aspect of emotions, this research aims to provide new insights into the dynamics of divine encounter and spiritual transformation that can be applied in a modern context.